Human immunodeficiency virus type 1 Vpu protein is an oligomeric type I integral membrane protein. - Maldarelli, F (1993)
The human immunodeficiency virus type 1 Vpu protein is a 16-kDa phosphoprotein which enhances the efficiency of virion production and induces rapid degradation of CD4, the cellular receptor for human immunodeficiency virus. The topology of membrane-inserted Vpu was investigated by using in vitro-synthesized Vpu cotranslationally inserted into canine microsomal membranes. Proteolytic digestion and immunoprecipitation studies revealed that Vpu was a type I integral membrane protein, with the hydrophilic domain projecting from the cytoplasmic membrane face. In addition, several high-molecular-weight proteins containing Vpu were identified by chemical cross-linking. Such complexes also formed when wild-type Vpu and a Tat-Vpu fusion protein were coexpressed. Subsequent analysis by one- and two-dimensional electrophoresis revealed that these high-molecular-weight complexes consisted of homo-oligomers of Vpu. These findings indicate that Vpu is a type I integral membrane protein capable of multimerization.